Pembangunan Sistem Informasi Perpustakaan Fakultas Ilmu Sosial Universitas Negeri Jakarta - Akbar, Adhitama; Ziveria, Mira (KALBISCIENTIA Jurnal Sains dan Teknologi, 2019)
As a reliable source of information on students, lecturers and campus community, Library of Faculty of Social Sciences, Jakarta State University must have a fast and precise process in service and data processing. Researchers design and build web-based information systems that can be used by librarians in running processes in the library, especially data processing and reports. System development is done with System Development Life Cycle (SDLC) Waterfall model. Then the system design is done by modeling language using Unified Modeling Language (UML). While the programming language used is PHP and HTML and database using MySQL. The final result of the design is a webbased library information system for Library of Faculty of Social Sciences, Jakarta State University with librarians as users of the system that can process library data and reports. System testing is done by Black Box testing by the system user (librarian), the result of the test can be concluded that the system has been as expected.